Adiposity is not beneficial to bone mineral density in 0–5 year old Chinese children: The Jiangsu bone health study. Issue 1 (January 2020) - Zhao, Yan; Qin, Rui; Ma, Xianghua; Qin, Zhenying; Yang, Zi; Hong, Hong; Lv, Heyu; Ye, Kan; Wei, Yarong; Zheng, Wen; Qi, Hongxia; Ni, Yufei; et al.
Highlights: Data on obesity in relation to BMD of children especially for infants under 2 years old were sparse. The Jiangsu bone health study is a large population-based cross-sectional multicenter study. The children were recruited by a stratified cluster random-sampling method in the Jiangsu Province, China. We also have taken into account the potential confounding variables affecting bone status. Adiposity is not beneficial to bone mineral density in 0-5 year old Chinese children. Abstract: Objective: Data on obesity in relation to bone mineral density(BMD) in infants and preschool children were sparse in China. The objective of this study was to examine the associations between body mass index (BMI) and BMD. Subjects and methods: This was a large population-based multicenter study in which the representative children aged 0–5 years were recruited from 13 Children's Health Care Centers by a stratified cluster random-sampling method in Jiangsu Province, China. BMD was measured by using quantitative ultrasound. The association of BMD with BMI and obesity were evaluated using multiple linear regression and logistic regression analysis taking into account the effects of confounders. The relations between age, weight, height, BMI and BMD were analyzed by using Pearson's correlation and further tested using partial correlation in the additive model. Results: A total of 5, 289 children (2786 boys and 2503 girls) were recruited. The BMD was positively linear relation with age, length/height, and was inversely linear relation with BMI ( r  = 0.711, P  < 0.001; r  = 0.727, P  < 0.001; r  = −0.318, P  < 0.001, respectively). The BMD gradually increased when the weight was in the range within 21.2 kg, but started to gain slowlyand even decreased when the weight was over 21.2 kg. After adjusting for confounders, compared with control group, children with obesityhad higher odds of low BMD (OR 95%CI: 2.73 (1.57, 4.76), P  < 0.001), the speed of sound (SOS)value in children with obesity was lower 47.45 (β = −47.45, 95%CI = −85.07, −9.83, P = 0.013). Conclusions: Adiposity was not advantageous for bone mineral density in 0-5-year-old Chinese children.